The Impact of international trade with China on economic growth of Myanmar (1990/91 - 2016/17) - NILAR, HLAING (KDI School, 2018)
The main objectives of this study are to estimate the long run equilibrium relationship among export and import between Myanmar and China and the GDP of Myanmar and the direction of long-run or short-run causality between the international trade among two countries and economic growth of Myanmar. The data used in this paper are time- series data collected from Ministry of Planning and Finance of Myanmar. The analysis is used to estimate the dynamic causal relationship between the international trade between Myanmar and China and GDP growth of Myanmar. In this study, the Augmented Dickey-Fuller (ADF) unit root test is used to determine whether there is the stationary relationship among the variables of Myanmar’s GDP and export and import with China after transforming them into first differences. The Johansen cointegrated test is used to determine whether all the data are cointegrated and they have long-run association. The Vector Error Correction Model is used to provide that export has a positive impact and import has a negative impact on GDP of Myanmar. The result is that there is a long-run causal relationship running from both exports and import to GDP, but not for short-run. This study shows that there is a long-run equilibrium relationship among the three variables; exports and imports with China and GDP of Myanmar.
Thesis(Master) --KDI School:Master of Public Policy,2018